(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Pathologic substrate of these forms of secondary tuberculosis is considered in detail. The possibilities and advantages of an innovative approach of valvular bronchial blocking used in complex treatment of destructive forms of pulmonary tuberculosis are presented. The technique enables to close completely the cavities in 70% of patients. The advantages of the method are described. The characteristics of clinical presentation and radiodiagnosis of the disease are given, and treatment techniques are presented.